(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This paper presents a clown woman’s experience of life in the hospital as a result of her journey on the street, her time at the university, and today as a researcher and teacher in a hospital. Based on the reports - called bobological reports - a reflection was made on the transforming power of clowning as a tool of subversion, whatever the performance environment. The first bobological report is based on the first visit to the hospital, a “clean face” visit (without acting as a clown), and the last two reports are after almost a year of acting.